2018
DOI: 10.2147/clep.s156210
|View full text |Cite
|
Sign up to set email alerts
|

Self-reported perinatal depressive symptoms and postnatal symptom severity after treatment with antidepressants in pregnancy: a cross-sectional study across 12 European countries using the Edinburgh Postnatal Depression Scale

Abstract: PurposeThis study aimed at exploring the prevalence of self-reported antenatal and postnatal depressive symptoms by severity across multiple countries and the association between antidepressant treatment in pregnancy and postnatal symptom severity.Materials and methodsThis was a multinational web-based study conducted across 12 European countries (n=8069). Uniform data collection was ensured via an electronic questionnaire. Pregnant women at any gestational week and mothers of children with <1 year of age coul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 45 publications
1
20
1
Order By: Relevance
“…Even though the evidence for the association was weak and its clinical relevance seems limited, this contrasting finding raises concerns about residual confounding by severity of maternal mental illness, and about the reliability of hardly ever self-harm classification on the EPDS item 10 [11,31]. At present, our and other available studies on antidepressants in pregnancy [44] do not document a benefit of antidepressant on self-harm reduction seen in observational studies among non-pregnant adults [15,48]. Because the interplay between the perinatal hormonal fluctuations and the pharmacological action of antidepressants remains elusive, we cannot exclude a more definite benefit of this drug treatment in pregnancy on other core symptoms of postpartum depression such as anhedonia or sadness [44,49].…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Even though the evidence for the association was weak and its clinical relevance seems limited, this contrasting finding raises concerns about residual confounding by severity of maternal mental illness, and about the reliability of hardly ever self-harm classification on the EPDS item 10 [11,31]. At present, our and other available studies on antidepressants in pregnancy [44] do not document a benefit of antidepressant on self-harm reduction seen in observational studies among non-pregnant adults [15,48]. Because the interplay between the perinatal hormonal fluctuations and the pharmacological action of antidepressants remains elusive, we cannot exclude a more definite benefit of this drug treatment in pregnancy on other core symptoms of postpartum depression such as anhedonia or sadness [44,49].…”
Section: Discussionmentioning
confidence: 77%
“…Because it is still debated whether antidepressants may increase the risk of SHI in younger adults individuals [17][18][19], we tested for an interaction term between antidepressant treatment in pregnancy and maternal age, as continuous variable and categorized as 17-24 years, 25-30, and over 30 years. To further elucidate this latter point, we used as positive control outcome the postpartum EPDS score on items 1-9, as we would expect reduced EPDS symptoms among medicated relative to non-medicated [44], via crude and weighted linear regression models. Because SHI was measured at different postpartum times, which is from childbirth to child age one year, we tested the interaction term between timing of SHI report and antidepressant use in pregnancy in the weighted models.…”
Section: Sensitivity Analysesmentioning
confidence: 99%
“…The research has demonstrated that patients who were treated with SSRI medications during pregnancy or patients who had not discontinued their previously started SSRI treatment were at a lower risk of onset or deterioration/ exacerbation of the condition in the postnatal period. It can be concluded that the optimum treatment with SSRI is indispensable in patients with the major depressive disorder [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nancy Melville in her study about the risk factors for suicide in women reported that 4% of women who died by suicide in Great Britain during the period 1997-2012 were in their perinatal period (a period that is a few weeks before delivery). The most common diagnoses in these women were depression, bipolar disorders and personality disorders [ 4 ] [ 5 ]. The most common symptoms included depressed mood, self-harm, suicidal ideas and hopelessness.…”
Section: Introductionmentioning
confidence: 99%
“…In the weighting procedure, each woman was assigned a weighting factor based on the population proportion per country divided by the sample proportion in each age-by-education stratum per country. Women under-represented in our sample were assigned a weight greater than 1, while those over-represented received a weight smaller than 1 33. The survey weight for the entire study sample had a mean of 0.93 (range 0.13–5.05).…”
Section: Participants and Methodsmentioning
confidence: 99%